Attenuation of the effects of fluoxetine on serotonergic neuronal activity by pindolol in rats - Rasmussen, Kurt; McCreary, Andrew C.; Shanks, Elaine A. (Neuroscience letters, 2004)
Based on its proposed ability to block the effect of selective serotonin reuptake inhibitors (SSRIs) on the firing rate of serotonergic neurons, the 5-HT 1A partial agonist/β-adrenergic antagonist pindolol has been examined in clinical trials for its ability to enhance the efficacy of SSRIs. However, varying results have been obtained in these clinical trials. To explore this issue, we examined the effects of pindolol alone and in combination with fluoxetine on the electrophysiological activity of serotonergic neurons in the dorsal raphe nucleus of anesthetized rats. Administration of pindolol (1, 5, and 20 mg/kg, s.c.) alone decreased the number of spontaneously active serotonergic neurons. Administration of fluoxetine (10 mg/kg, i.p.) alone also decreased the number of spontaneously active serotonergic neurons. However, when administered following fluoxetine, pindolol significantly attenuated, but did not block completely, the inhibitory effects of fluoxetine on the number of spontaneously active serotonergic neurons. These results indicate that pindolol can attenuate the effects of fluoxetine on the firing of serotonergic neurons. These results may help explain the varying efficacy of pindolol in clinical trials with SSRIs.